Restoring Trust in Journalism: An Education Prescription. (March 2020) - Reed, Katherine; Walsh-Childers, Kim; Fischer, Kenneth; Davie, Bill
The practice of journalism has long been based on the premise that a receptive audience awaits the content and that citizens—as participants in a democracy—will use the news to make sound decisions. Yet mainstream journalism has lost much of its audience to purveyors of disinformation, misinformation, and malinformation, a situation that has grown more perilous with the widespread embrace of social media tools in all their sophistication. This represents a threat to the vital forums of democracy and a new challenge for journalism education: How to equip future journalists with the critical thinking and technology skills they need to produce and/or share content that is independent, accurate, and fair, while developing relationships with audiences that reflect accountability, respect, and understanding. Journalists also need to learn how to identify situations that call for careful consideration of audience confirmation biases and accordingly to present important information, such as on vaccines, in a manner less likely to trigger those biases. The mix of new skills required in this complicated, sometimes toxic, information environment is the subject of this essay.